La réserve autochtone « transfrontalière » d’Akwesasne entre Canada et États-Unis, zone de contrebande et faille dans la sécurisation de la frontière - Guillaume Poiret; Pierre-Alexandre Beylier (Territoire en Mouvement)
The border between Canada and the United States of America has evolved dramatically after the terrorist attacks of 9/11. The 49th parallel is now more controlled since the US has undertaken a securitization of its borders. However, at the same time, Washington also tries to prevent the new policy from hindering the intensity of the economic exchanges which occur daily across the border. Nevertheless, this policy encounters a specific obstacle, the Mohawk reserve of Akwesasne located on the border of the two countries. Straddling Quebec, Ontario and the State of New York, the reserve has a specific status which forbids any controls of the border patrols inside and law enforcement operations. This situation accounts for the fact that the reserve is attractive for traffickers. New nation-wide networks operating there are creating changes in the local daily life of both the inhabitants of the reservation and those living around. Using datas collected from the police archives and interviews with local authorities, this paper aims to explain those evolutions and determine the nature and structure of the new traffics including their spatial extension, also describing the new policies implemented at the border to counter the traffics.